Craniocervical junction involvement in ankylosing spondylitis - Slobodin, Gleb; Shpigelman, Arsen; Dawood, Hanna; Rimar, Doron; Croitoru, Simona; Boulman, Nina; Rozenbaum, Michael; Kaly, Lisa; Rosner, Itzhak; Odeh, Majed (European spine journal, 2015)
Purpose Available studies of craniocervical junction (CCJ) involvement in ankylosing spondylitis (AS) are based on conventional radiography, which has limited ability in the definition of many elements of the CCJ. The goal of the present study was to describe the spectrum of computed tomography (CT) findings in the CCJ in a cohort of patients with AS. Methods CT scans of the cervical spine of 11 patients with AS and 33 control subjects were reviewed, and imaging findings related to the CCJ were assessed. The standard anatomic intervals describing the CCJ were measured and compared to accepted normal standards. Findings representing pathology were described, categorized by localization, and relation to joints or ligaments of the CCJ. Results All AS patients were males with median age of 48 years and median disease duration of 20 years. The calculated median-modified Stoke Ankylosing Spondylitis Spinal Score (mSASSS) for the cervical spine was 8.5 ranging from 0 to 27. Disease-related changes in one or more elements of the CCJ were detected in all patients. Atlanto-occipital joints were involved in 8 patients, while 3 patients had disease of the atlanto-dental articulation. Enthesopathy of the CCJ was observed in 7 patients. Conclusions The CCJ is frequently involved in AS patients with advanced disease and may be independent on the mSASSS. Both articulations and ligaments of CCJ may be affected in AS patients.